A technique for the selective detection of neutrons in geological applications - Baker, J.H.; Galunov, N.Z.; Kostin, V.G.; Martynenko, E.V.; Tarasenko, O.A. (Вопросы атомной науки и техники, 2007)
We present a new, combined technique for the detection of fast and thermal neutrons in the presence of accompanying gamma radiation, for geological and radioecological applications. To separate the slow neutron pulses and fast gamma pulses of organic scintillators, we used the method of particle identification by radioluminescence pulse shape. The device has been tested by the combined neutron and gamma radiation sources ²⁵²Cf and ²³⁹Pu-Be, and by a 14.2 MeV D-T source of fast neutrons both in the laboratory, and under real, field conditions as applied at selected sites of the European Union. Розглянуті основні принципи та апаратура для реєстрації швидких і теплових нейтронів для сучасних задач геології й радіоекології. Роздільна реєстрація повільних нейтронних імпульсів і швидких імпульсів гама-випромінювання органічних сцинтиляторів здійснювалася шляхом дискримінації іонізуючого випромінювання за формою сцинтиляційного імпульсу. Атестація апаратури проводилася за допомогою джерел ²⁵²Cf та ²³⁹Pu-Be , а також D-T джерела швидких нейтронів з енергією 14.2 МеВ, як у лабораторних умовах, так і в реальних умовах її застосування в ряді країн Європейського Союзу. Изложены основные принципы и аппаратура для регистрации быстрых и тепловых нейтронов для современных задач геологии и радиоэкологии. Раздельная регистрация медленных нейтронных импульсов и быстрых импульсов гамма-излучения органических сцинтилляторов осуществлялась путем дискриминации ионизирующего излучения по форме сцинтилляционного импульса. Аттестация аппаратуры производилась с помощью источников ²⁵²Cf и ²³⁹Pu-Be , а также D-T источника быстрых нейтронов с энергией 14.2 МэВ, как в лабораторных условиях, так и в реальных условиях ее применения в ряде стран Европейского Союза.